E-reservation restaurant - Lim, Kai Yi (2024)
This project develops an innovative e-Reservation Restaurant web application aimed at revolutionizing online restaurant booking systems. The existing similar platforms have various limitations, such as limited search filters that make it difficult to find the perfect restaurant, and a lack of reminders for customers’ restaurant bookings can lead to high no-show rates due to customers forgetting about their bookings. Moreover, contacting customer support for reservation or website inquiries can be frustrating, as it lacks the efficiency of a live representative. Hence, this project seeks to overcome these issues by creating a revolutionary e-Reservation Restaurant website using the Agile methodology. The core motivation of this project is to address the problems faced by existing online restaurant booking systems to create an enhanced user-centric experience. This system empowers users with a personalized recommendation engine that enables users to select their preferences, such as cuisine type and desired location. The website then automatically recommends restaurants that align with the customer’s individual needs. This not only saves users time searching but also introduces them to new dining options they might not have otherwise known about. Additionally, the system incorporates an "Add to Google Calendar" event function in the restaurant booking confirmation e-mail, providing a friendly reminder in case customers forget about their booking. This benefits diners and optimizes restaurant revenue and table management by reducing no-show rates. To further enhance the user experience, the system incorporates cutting-edge AI-powered features such as an AI chatbot to assist users with reservations and website inquiries, providing immediate and convenient support, unlike the current limitations of many platforms. By combining these functionalities, the system aims to significantly improve the customer experience and satisfaction. Diners can anticipate a more streamlined and enjoyable reservation process, while restaurants can expect a reduction in no-show rates and an overall improvement in table management.